Comparing perceptions of the impact of journal rankings between fields. (January 2023) - Brooks, Chris; Schopohl, Lisa; Walker, James T.
Abstract: While the purpose of academic research is to obtain new knowledge and understanding, there is an increasing concern that many scholars value work based upon where it is published rather than on its intrinsic quality. We argue that the degree to which journal ranking lists affect research has an important field-specific component. Using a large-scale survey of UK business academics and underpinned with a conceptual framework inspired by Bourdieu, we examine the attitudes towards journal ranking lists of individuals working within 22 'fields' operating under the umbrella of business and management in the Academic Journal Guide (AJG). We show that scholars in economics and finance at one end of the spectrum, and in organisational studies at the other, systematically differ from accounting scholars in how they relate to the list. While the empirical evidence suggests that finance and economics are more insular than other fields, members of these two fields are the ones who are significantly less likely to consider that journal lists create a 'research monoculture', foster 'technically well-executed but boring research', or 'encourage work that is not of interest to practitioners/policy makers'. On the other hand, scholars in organisational studies show the highest agreement with these concerns about journal ranking lists. Our findings have important implications for the evolution of accounting as a field that spans both a critical, interpretive paradigm with a strong focus on organisational context as well as a positivist, financial and capital markets-based research paradigm. If accounting scholars of these two approaches attach different authority to journal ranking lists and the value of publications in highly ranked journals, these perception differences could lead to tensions within the field and could have distortive effects on resource allocations and the career prospects of accounting scholars working in the respective sub-fields.